Aortic stenosis reexpanded – a novel approach to determine aortic valve area with phase contrast cardiovascular magnetic resonance imaging. (14th October 2021) - Troger, F; Lechner, I; Reindl, M; Tiller, C; Holzknecht, M; Pamminger, M; Kremser, C; Reinstadler, S J; Bauer, A; Metzler, B; Mayr, A; Klug, G
Abstract: Background: Transthoracic echocardiography (TTE) has become the diagnostic standard for evaluating aortic stenosis (AS) severity, mainly because of its advantages in comparison to the gold standard of cardiac catheterization. However, its inaccuracies in determining stroke volume (SV) and consequentially computing aortic valve area (AVA) call for a more precise and dependable method. Phase contrast cardiovascular magnetic resonance imaging (PC-CMR) is an aspiring tool to push these boundaries. Purpose: The aim of this study was to validate a novel and simple approach based on PC-CMR against the invasive and echocardiographic determination of SV and AVA in patients with moderate and severe AS. Methods: A total of 50 patients with moderate or severe AS underwent TTE, cardiac catheterization and CMR; AVA by PC-CMR was determined via plotting momentary flow across the valve against momentary flow velocity. SV via CMR was measured directly via PC-CMR and volumetrically using cine images. Invasive SV and AVA were determined via Fick principle and Gorlin formula, respectively. TTE yielded SV and AVA using the continuity equation. Finally, gradients were calculated via the modified Bernoulli equation. Results: SV by PC-CMR showed a strong correlation with cine-CMR with no significant bias (r: 0.730, p<0.001; SV by PC-CMR: 85±31ml; SV by cine-CMR: 85±19ml, p=0.829). Peak gradients determined by PC-CMR were 65±29mmHg and correlated inversely with AVA by PC-CMR (r: −0.371; p=0.008). Mean AVA during the whole systolic phase showed a moderate correlation (r: 0.544, p<0.001) to invasive AVA with a small bias (AVA by CMR: 0.78±0.25cm 2 versus invasive AVA: 0.70±0.23cm 2, bias: 0.08cm 2, p=0.017). Inter-methodical correlation and bias of AVA as measured by TTE and invasive AVA (AVA by TTE: 0.81±0.23cm 2, r: 0.580, p<0.001, bias 0.11cm 2, p<0.001) were similar to AVA by PC-CMR and invasive AVA. Conclusion: PC-CMR provides a great option to yield reliable and solid SV values in patients with moderate and severe AS. Furthermore, continuous determination of flow volumes and flow velocities is able to determine AVA in these patients in an easy and reproducible manner. Our novel approach shines a light on the diagnostic potential of PC-CMR for non-invasive AS grading, especially in cases where echocardiography reaches its limits and where clinical findings appear inconclusive. Funding Acknowledgement: Type of funding sources: None.